A Constraint-Led Approach to Coaching and Teaching Games: Can going back to the future solve the «they need the basics before they can play a game» argument? (Agora for Physical Education and Sport, 2018)
Despite the continued popularity of Games Centred Approaches with tertiary level academics, the take-up by practitioners has been limited. In a recent survey of entry level HPE students undertaken at our university, 95% reported that they had received a predominantly traditional experience in school physical education lessons. This finding is in line with a common response when we engage with practitioners who strongly advocate the need for games players to learn the basics before they can play a game. In this paper we will present concepts and practical exemplars demonstrating a Constraint-Led Approach (CLA) to games teaching and coaching. We will show that adopting a CLA has the potential to provide practitioners with the tools to address this significant barrier and potentially enhance the adoption of games-based approaches. We will argue that the technique-tactics dichotomy is a redundant framework as the intentions and actions of learners is a function of their current action capabilities. However, we will also propose that games-based practitioners need to develop pedagogical practices that initially develop intra-individual-environment co-ordination before moving onto a more traditional focus on inter-individual-environment co-ordination (i.e., how teams organise to solve games-based problems). A key focus will be on the need to consider the mutuality of the individual and the environment and how backyard games allied to CLA methods can help practitioners design better games based programmes that will meet the needs of all games players irrespective of age or ability level.
Keywords: Backyard games; constraints-led approaches; game centred approaches; ecological dynamics; nonlinear pedagogy